Pengaruh Reward System Terhadap Kinerja Perusahaan (Studi Empiris pada Perusahaan Busana Remaja Agracipta Yogyakarta) - Kurniasari, Riza; Dus Reis Doa, Ajita Da Silva; Kon, Iknasius; Kirana, Kusuma Chandra (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The main objective of this study is to investigate the extent to which rewards affect the performance of Agracipta Teenage Busana company. The research utilized a quantitative explanatory method based on the S-R theory. Data was collected through questionnaires from a population of 3,000 Busana Teenage Agracipta employees, selected using a simple random sampling technique. Simple linear regression was employed to measure the impact of independent variable (X) on the dependent variable (Y). Data from the questionnaires were analyzed using Statistical Product and Service Solutions (SPSS) version 24. Based on the findings from the simple linear regression, it was discovered that rewards have 35.3% effect on the performance of Agracipta Teenage.